Nuclear DNA endoreplication and plastid index in mesophyll of some dicotyledonous species - Barbara Damsz; Piotr Łuchniak (Acta Societatis Botanicorum Poloniae, 2014)
Cytophotometric studies of nuclear DNA content after Feulgen procedure indicate that in mesophyll of all the seven studied species the highest nuclear DNA endoreplication level occurs in II or III leaf and it varies for particular species. No differences were found in nuclear DNA endoreplication dynamics between the basal and apical parts of the leaf blade. Chloroplast number per cell generally decreases in the successive leaves, and the plastid index is the smallest in the first (oldest) leaves, being similar in both zones. In four species chloroplast number and plastid index show relatively low negative correlation with nuclear DNA contents (expressed as endoreplication index), in two species this correlation is positive, and one species displays very low r value.